Feminist Existentialism as Portrayed in the Movie Hidden Figures - Mahadewi, Ni Putu Yona; Rajeg, Gede Primahadi Wijaya; Krisnawati, Ni Luh Putu (ENGLISH JOURNAL OF INDRAGIRI, 2026)
Feminist existentialism highlights the struggles women face in societies that impose restrictions based on gender and societal expectations. This study aimed to explore how the movie Hidden Figures portrays feminist existentialism ideology through the experiences and resistance of its main characters. Using a qualitative research method, the study examined the duality of the sexes and the various forms of women’s resistance as depicted in the film. Data collection was carried out through documentation and note-taking techniques. The analysis employed Simone de Beauvoir’s feminist existentialism framework as its primary theoretical foundation to examine how the movie Hidden Figures represents gender duality and feminist existentialism through the resistance of its main female characters, focusing on the identification of gender duality, the evaluation of acts of resistance, and the contextualization of these themes within the discourse of feminist existentialism. The findings reveal that Hidden Figures present a clear depiction of gender duality, where women are marginalized in workplaces, education, and social spaces. Despite these limitations, the main characters resist societal restrictions by asserting themselves in professional fields, intellectual discourse, and social transformation, aligning with the feminist existentialism concept of transcendence. Through their struggles, the film challenged traditional gender norms and contributes meaningfully to discussions on gender equality.